Sustaining Cape Town Imagining a Livable City - Swilling, Mark (African Sun Media, 2010)
Although cities constitute the key contributors to unsustainable development, especially due to their ecological and equity impacts, they are also viewed as the vehicle for the transition to a sustainable future for humanity both in terms of technologies as well as policies and lifestyle changes. This book introduces the theoretical principles which underpin the required transition to sustainable cities in general and Cape Town in particular. The subsequent fourteen chapters tackle more specific areas of interventions and the key constraints towards realisation of related transition interventions in the city of Cape Town.